Clonal analysis of three morphologically distinct lymphomas occurring in the same patient. Issue 11 (November 1994) - McCormick, C; Philp, E; Mansi, J; Livni, N; McCarthy, K
Abstract : AIMS--To determine whether three morphologically distinct lymphomas (mucosa associated lymphoid tissue (MALT) lymphoma, monocytoid B cell lymphoma, and large cell anaplastic lymphoma), which occurred in the same patient, were in fact three morphological variants of the same lymphoproliferative process. METHODS--Previously described methods of clonal analysis using the polymerase chain reaction (PCR) were used to determine the pattern of rearrangements of the immunoglobulin heavy chain gene and the T cell receptor beta and T cell receptor gamma chain genes in the three lymphomas. RESULTS--All three morphological entities had identical patterns of gene rearrangements. CONCLUSIONS--This finding confirms the association between MALT lymphoma and monocytoid B cell lymphoma, and also provides evidence that large cell anaplastic lymphoma may not only arise de novo but may also be an end stage morphological picture in lymphoma progression.